(3EjVGM GdCMcGe deG jCNPg GdYeGd hGdMcGes - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s
(3ChdgG (B:s
,(3HYO , agPG cJGH YOje GdfXQ ai HGHg , ebQQ GddMb ai fUGHg , eTJed Ydi JMQjQGJ GdeJbOejf , hCHMGK GdeJCNQjf HChVM HjGf s
(3BNQgG (B:s
(3agPg gOjI HYK YdjgG LGg GdSdWGf, abjd JQO hbjd JhVY ai HjJ GdeGd ddeSedejf GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfGhjjf hGdcdeGJ HGdMeQI s
(3Ydi ghGeTgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdeYGQa GdYGeIs